EROS AND THANATOS INJULIAN BARNES‟ THE SENSE OF AN ENDING – A PSYCHOLOGICAL STUDY - Priya, I. Angeline (International Journal of Psychosocial Rehabilitation, 2020)
The novel The Sense of an Ending written by Julian Barnesfocused sex and death, through the characters of Anthony Webster and Adrian Finn. This novel runs around the death of four characters. Tony Webster is the narrator of this novel.The title of the novel Eros and Thanatos indicate love and death. It is a Greek terms and Sigmund Freud was the founder of this terms. Eros means love, but in this novel it is mentioned as sex not love.This Sigmund’s theory resembled with the characters of Miss. Veronica Ford and Mrs. Sarah Ford. In this novel Julian Barnes clearly depicted the struggle of being woman in the modern society in psychological aspect.